A Giant Coronary Artery Aneurysm with Coronary Arteriovenous Fistula in Asymptomatic Elderly Patient - Caterina Milici; Daniella Bovelli; Valentino Borghetti; Georgette Khoury; Marco Bazzucchi; Massimo Principi; Marcello Dominici; Enrico Boschetti (Case Reports in Vascular Medicine)
Coronary Arteriovenous Fistula (CAF) is a rare defect that occurs in 0.1-0.2% of patients undergoing coronary angiography; Coronary Artery Aneurism (CAA) also occurs in approximately 15–19% of patients with CAF. It is usually congenital, but in rare occasions it occurs after chest trauma, cardiac surgery, or coronary interventions. The case described is that of a 72-year-old woman, without previous history of cardiovascular disease, who presented a huge cardiac mass. A multimodal approach was necessary to diagnose a giant CAA with CAF responsible for compression and displacement of cardiac structures. Due to likely congenitally origin of the lesion and the absence of symptoms correlated to the CAA and to the CAF we decided to avoid invasive interventions and to treat the patient with medical therapy.